Effects of sodium bicarbonate on lactate levels during supramaximal exercise - Brewester, Ellen (My University, 1984)
Aerobically trained females (n=15) performed 4 supramax exercise bouts 1 hr after orally ingesting either 200 mg/kg body wt. NaHCO3 or 5.0 g. NaC1, to determine the effects of NaHCO3 on blood lactate concentration. Using a double blind protocol, each S performed 4 randomized conditions: 1) NaC1-30 sec, 2) NaC1-time to exhaustion (TTE), 3) NaHCO3-30 sec, 4) NaHCO3-TTE. The Wingate Anaerobic Test was used to elicit supramax exercise. 4 ml samples of blood were drawn from the antecubital vein 30 min post-ingestion and 5 min post-exercise in each of the 4 conditions. Lactic acid (LA) was determined using the enzymatic method described by Sigma Chemical Co. (1977). Pedal revolutions were recorded for determination of total work (TW). Statistical analysis of the data revealed no sig (p > .05) diff in TW, post-ingestion LA, NaHCO3 (7 mg%), NaC1 (6 mg%), and TTE-LA, NaHCO3 (88 mg%), NaC1 (81 mg%). However, in the 30 sec trial, LA levels were sig (p < .05) higher with NaHCO3 (73 mg%), than NaC1 (62 mg%). This increased LA with NaHCO3 was attributed to improved efflux of LA across the sarcolemma. The explanation for no sig diff in TTE-LA was unclear, perhaps an error in test protocol. Based on these results, it appears that while NaHCO3 may improve efflux of LA, it does not improve performance in short-term supramax exercise.
Keywords: Sodium bicarbonate -- Physiological effect; Lactic acid -- Physiological aspects